Cross-border banking and business cycles in asymmetric currency unions - Lena Dräger; Christian R. Proa\~no (Deutsche Bundesbank, 2015)
Against the background of the recent housing boom and bust in countries such as Spain and Ireland, we investigate in this paper the macroeconomic consequences of cross-border banking in monetary unions such as the euro area. For this purpose, we incorporate in an otherwise standard two-region monetary union DSGE model a banking sector module along the lines of Gerali et al. (2010), accounting for borrowing constraints of entrepreneurs and an internal constraint on the bank's leverage ratio. We illustrate in particular how different lending standards within the monetary union can translate into destabilizing spill-over effects between the regions, which can in turn result in a higher macroeconomic volatility. This mechanism is modeled by letting the loanto-value (LTV) ratio that banks demand of entrepreneurs depend on either regional productivity shocks or on the productivity shock from one dominating region. Thereby, we demonstrate a channel through which the financial sector may have exacerbated the emergence of macroeconomic imbalances within the euro area. Additionally, we show the effects of a monetary policy rule augmented by the loan rate spread as in Cúrdia and Woodford (2010) in a two-country monetary union context.
Keywords: F41; F34; E52; 330; cross-border banking; euro area; monetary unions; DSGE; monetary policy